2022-VA-1146-ESGO Conservative endoscopic management of a colorectal leakage in advanced ovarian cancer. (20th October 2022) - Boria, Felix; Riesco, Jose Maria; Gutierrez, Monica; Chacón, Enrique; Vazquez, Daniel; Manzour, Nabil; Castellanos, Teresa; Chiva, Luis
Abstract : Introduction/Background: Anastomotic leakage in advanced ovarian cancer is a major concern. Relaparotomy, washings and a protective stoma may be the solution in most cases. However, in some selected patients, with leaks collected to the pelvis, a conservative management can be done. In this case we performed a conservative endoscopic management in two times. First, we drained the collection, and then we sutured the defect endoscopically Methodology: Video edited Results: Conclusion: